Science education and the integration of English for learning: study of one CLIL approach in a Portuguese lower secondary school - Piacentini, Valentina (2020)
The development of meaningful environments for the learning of Science and foreign languages at school is a concern for education, whose purpose should be, at a global level, also scientific literacy and language proficiency of students. Research on the integration of Science education with English learning as well as on the Language focus for Science education is thus highly relevant. Diverse languages are used within Science education, beyond the verbal, such as the visual, mathematical, operational languages through the Science doing, exploring, arguing, etc. and in meaning making for knowledge construction. Teachers are not always aware of the learning difficulty students may have with these languages, even when their mother tongue is the language of instruction. Previous studies have revealed that teaching practices aware of language and other semiotic modes implied in Science are beneficial for the learning of Science. CLIL (Content and Language Integrated Learning) is, actually, a possible educational approach, based on the principle that languages are learnt while they are used in socially significant activities, aiming both at the learners’ understanding of content (a specific subject or part of it) and at the acquisition of an additional (foreign or second) language. Conceived for the students’ acquisition of the foreign Language while in use during classes of the specific Content, CLIL is an example of cross-curricular education, entailing authentic learning settings and strategies more centred on learners. Furthermore, CLIL can represent a research context to gauge the importance of a language-aware teaching as in the case with the CLIL-type “English Plus” project (EP), in which Science is taught and learnt with and in English at lower secondary grades of one state school in North Portugal. Our research questions were focused on the understanding of 1) the practices of Language(s) within Science education in the (EP) teachers’ and students’ experience and 2) the relationship between the presence of English and EP Science provision. We designed a descriptive-explanatory case study of the EP project, in the 2015-2016 school year, embedding participants involved in the programme at different times and levels (two English and two Science teachers; 11 former and 96 current EP students, in relation to the year of our empirical study). Owing to the contextual conditions of the EP project, an ethnographic approach was undertaken, for the researcher to become familiar with it and its actors. We collected data from these different sources through a diversity of techniques: teacher and former student semi-structured interview; current student semi-structured questionnaire; non-structured “at-different-degree” participant observation of classroom practices, lesson planning and other contexts; collection of school and teacher documents. Inductive content analysis of transcribed interviews and open-ended answers to questionnaire was performed. A descriptive statistical analysis of closed-ended answers to student questionnaire as well as a reading of the researcher’s field notes and school documents complemented the understanding, triangulating the information. Results brought independent evidence of a greater teacher awareness of the use of languages (verbal language in the mother tongue or English, and other representation modalities) when an additional language is also present for Science education. In other words, because of the presence of English, a (subject) teacher may become open to the student’s (language) learning difficulties and learning styles and to changing strategies and resources. Therefore, besides the clear benefit of advancement in the English proficiency, a language-aware teaching methodology (also when the mother tongue is spoken) also emerges, important to improve the education of the specific subject and, consequently, student learning. In turn, this opens reflection on teacher practices and education for and about the learning of Science, and further opportunities for investigation. Our study increases the research on CLIL in Portugal and, among other contributions, enriches the field of study on CLIL and non-CLIL Science practice.